Possible mechanisms underlying abundance and diversity responses of nematode communities to plant diversity. Issue 5 (19th May 2017) - Cortois, Roeland; Veen, G. F. (Ciska); Duyts, Henk; Abbas, Maike; Strecker, Tanja; Kostenko, Olga; Eisenhauer, Nico; Scheu, Stefan; Gleixner, Gerd; De Deyn, Gerlinde B.; van der Putten, Wim H.
Abstract: Plant diversity is known to influence the abundance and diversity of belowground biota; however, patterns are not well predictable and there is still much unknown about the driving mechanisms. We analyzed changes in soil nematode community composition as affected by long‐term manipulations of plant species and functional group diversity in a field experiment with plant species diversity controlled by sowing a range of 1–60 species mixtures and controlling non‐sown species by hand weeding. Nematode communities contain a variety of species feeding on bacteria, fungi, plants, invertebrates, while some are omnivorous. We analyzed responses of nematode abundance and diversity to plant species and functional diversity, and used structural equation modeling (SEM) to explore the possible mechanisms underlying the observed patterns. The abundance of individuals of all nematode feeding types, except for predatory nematodes, increased with both plant species and plant functional group diversity. The abundance of microbial‐feeding nematodes was related positively to aboveground plant community biomass, whereas abundance of plant‐feeding nematodes was related positively to shoot C:N ratio. The abundance of predatory nematodes, in turn, was positively related to numbers of plant‐feeding nematodes, but not to the abundance of microbial feeders. Interestingly, the numbers of plant‐feeding nematodes per unit root mass were lowest in the high‐diversity plant communities, pointing at reduced exposure to belowground herbivores when plants grow in species‐diverse communities. Taxon richness of plant‐feeding and microbial‐feeding nematodes increased with plant species and plant functional group diversity. Increasing plant functional group diversity also enhanced taxon richness of predatory nematodes. The SEM suggests that bottom‐up control effects of plant species and plant functional group diversity on abundance of nematodes in the various feeding types predominantly involve mechanistic linkages related to plant quality instead of plant quantity; especially, C:N ratios of the shoot tissues, and/or effects of plants on the soil habitat, rather than shoot quantity explained nematode abundance. Although aboveground plant properties may only partly serve as a proxy for belowground resource quality and quantity, our results encourage further studies on nematode responses to variations in plant species and plant functional diversity in relation to both quantity and quality of the belowground resources.